Membumikan Teologi Transformatif Penyetaraan Sosial Umat - Robikah, Siti (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2017)
This article describes the renewal of Moeslim's Islamic thinking about transformative theology, and aims to introduce and revitalize Islamic thought that is almost forgotten. Islam as a foundation for the life of Muslims should not only prioritize the hablum min Allah and forget the hablum min an-nas, both must be balanced. This research is a reseacrh library, and the work of Moeslim Abdurrahman as the primary data. According to Moeslim worship in particular 'must be balanced with social care. This has become Moeslim's anxiety when he sees the reality of Muslims today being colonized by the flow of modernization which has led to the development of western capitalism, thus impacting increasing poverty and ignorance in Indonesia. This study yields findings that in transformative theology Moeslim offers reforms in the field of economics and education through community empowerment with job creation and the realization of a new model of pesantren which gives birth to Muslim thinkers based on liberation of oppression as the main objective of transformative theology.